Αv integrins on mesenchymal cells regulate skeletal and cardiac muscle fibrosis. Issue 1 (December 2017) - Murray, I.; Gonzalez, Z.; Baily, J.; Dobie, R.; Wallace, R.; Mackinnon, A.; Smith, J.; Greenhalgh, S.; Thompson, A.; Conroy, K.; Griggs, D.; Ruminski, P.; et al.
Abstract Mesenchymal cells expressing platelet-derived growth factor receptor beta (PDGFRβ) are known to be important in fibrosis of organs such as the liver and kidney. Here we show that PDGFRβ+ cells contribute to skeletal muscle and cardiac fibrosis via a mechanism that depends on αv integrins. Mice in which αv integrin is depleted in PDGFRβ+ cells are protected from cardiotoxin and laceration-induced skeletal muscle fibrosis and angiotensin II-induced cardiac fibrosis. In addition, a small-molecule inhibitor of αv integrins attenuates fibrosis, even when pre-established, in both skeletal and cardiac muscle, and improves skeletal muscle function. αv integrin blockade also reduces TGFβ activation in primary human skeletal muscle and cardiac PDGFRβ+ cells, suggesting that αv integrin inhibitors may be effective for the treatment and prevention of a broad range of muscle fibroses. The mechanisms underlying tissue fibrosis are unclear. The authors show that mesenchymal cells expressing PDGFRβ mediate fibrosis in skeletal muscle and heart via a mechanism involving αv integrin, and that inhibitors of αv integrins attenuate fibrotic responses in mice.